Survival Comes at a Cost: A Coevolution of Phage and Its Host Leads to Phage Resistance and Antibiotic Sensitivity of Pseudomonas aeruginosa Multidrug Resistant Strains - Koderi Valappil, Sarshad; Shetty, Prateek; Deim, Zoltán; Terhes, Gabriella; Urbán, Edit; Váczi, Sándor; Patai, Roland; Polgár, Tamás; Pertics, Botond Zsombor; Schneider, György; Kovács, Tamás; Rákhely, Gábor (Frontiers in Microbiology, 2021)
The increasing ineffectiveness of traditional antibiotics and the rise of multidrug resistant (MDR) bacteria have necessitated the revival of bacteriophage (phage) therapy. However, bacteria might also evolve resistance against phages. Phages and their bacterial hosts coexist in nature, resulting in a continuous coevolutionary competition for survival. We have isolated several clinical strains of Pseudomonas aeruginosa and phages that infect them. Among these, the PIAS (Phage Inducing Antibiotic Sensitivity) phage belonging to the Myoviridae family can induce multistep genomic deletion in drug-resistant clinical strains of P. aeruginosa, producing a compromised drug efflux system in the bacterial host. We identified two types of mutant lines in the process: a green mutant with SNPs and smaller deletions and a red mutant with large (~250 kbp) genomic deletion. We demonstrated that PIAS used the OprM-MexXY system to initiate the infection. P. aeruginosa clogged PIAS phage infection by either modifying or deleting these receptors. The green mutant gaining phage resistance by SNPs could be overcome by evolved PIASs (E-PIASs) with a mutation in its tail-fiber protein. Characterization of the mutant phages will provide a deeper understanding of phage-host interaction. The coevolutionary process continued with large deletions in the same regions of the bacterial genomes to block the (E-)PIAS infection. These mutants gained phage resistance via either complete loss or substantial modifications of the phage receptor, OmpR-MexXY, negating its essential role in antibiotic resistance. In vitro and in vivo studies indicated that combined use of PIAS and antibiotics could effectively inhibit P. aeruginosa growth. The phage can either eradicate bacteria or induce antibiotic sensitivity in MDR-resistant clinical strains. We have explored the potential use of combination therapy as an alternative approach against MDR P. aeruginosa infection.